The golden hour in infants <29 weeks of gestational age - Valérie Gonçalves Vieira (2019)
Objective. There is still few evidence and research about the best intervention for the extreme low gestational age newborn (ELGAN) in the delivery room and neonatal intensive care unit (NICU). The main goal of this investigation was to evaluate the impact of the golden hour variables in early outcomes and mortality rate, specifically in infants less than 29 weeks of gestational age (GA). Methods. Data from 101 newborns with <29 weeks of GA admitted to our level III NICU between June 2011 and June 2018 were analyzed retrospectively. Information about demographics, prenatal, delivery room, interventions after birth, NICU stay and outcomes were recorded. A regression model was used to predict the factors that affect early neonatal outcomes. Results. Our study showed an association between oxygen and bronchopulmonary dysplasia (BPD) (odds ratio (OR) 1.50; 95% confidence interval (95%CI) 1.01-2.24; p=0.045 ); systolic pressure to intraventricular hemorrhage (IVH) ≥ grade 3 (OR 1.37; 95%CI 2.035-4.014; p=0.019); glucose was protective to patent ductus arteriosus (PDA) (OR 0.97; 95%CI 0.955-0.994; p=0.010 ); and continuous positive airway pressure (CPAP) in the NICU was protective to death (OR 0.011; 95%CI 0.101-0.401; p=0.014). We did not find any statistically significant independent associations between temperature, post-natal steroids and infection, with short term outcomes. The overall mortality rate for newborns in our center of care was 33.7% with a median (min-max) length of hospital stay of 60 days (1-191). Conclusions. The first minutes after birth have a big impact in neonatal outcomes.